Europe and America : the prospects for partnership - Peterson, John, 1958- (Routledge, 1996)
The conflict in Bosnia, disputes within the new World Trade Organizatiion and debates about NATO enlargement all illustrate a single point: no relationship is more important in determining the state of international relations than the alliance between Europe and America. Contrary to accepted wisdom, John Peterson argues that the end of the Cold War actually enhances the prospects for partnership between the United States and the European Union. Completely updated, this book offers a clear and penetrating analysis of the problems and opportunities facing the transatlantic alliance.